2017
DOI: 10.1007/s11356-017-9609-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crude oil exposure on cardiac function and thermal tolerance of juvenile rainbow trout and European sea bass

Abstract: Oil spills pose a threat to aquatic organisms. However, the physiological effects of crude oil on cardiac function and on thermal tolerance of juvenile fish are still poorly understood. Consequently, in this paper, we will present results of two separate experiments where we exposed juvenile rainbow trout and European sea bass to crude oil and made cardiac thermal tolerances and maximum heart rate (f ) measurements after 1 week (rainbow trout) and 6-month recovery (sea bass). In both species, the f was lower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…It also seems to contradict the high critical thermal maximum (CT max ) of European seabass (28.12±0.09 to 32.50±0.04°C in Mauduit et al, 2016;and 31.3±0.3°C in Anttila et al, 2017). However, in seabass acclimated to 17°C, Anttila et al (2017) found arrhythmia occurred at around 22°C, although CT max was above 30°C. Furthermore, the Arrhenius breakpoint temperature for maximum heart rate, which is connected to the thermal optimum of growth and aerobic scope, was 19.3±0.3°C and the temperature with the highest maximal heart rate, a measure of the thermal limits of cardiac function, was 21.8±0.4°C in these fish (Anttila et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It also seems to contradict the high critical thermal maximum (CT max ) of European seabass (28.12±0.09 to 32.50±0.04°C in Mauduit et al, 2016;and 31.3±0.3°C in Anttila et al, 2017). However, in seabass acclimated to 17°C, Anttila et al (2017) found arrhythmia occurred at around 22°C, although CT max was above 30°C. Furthermore, the Arrhenius breakpoint temperature for maximum heart rate, which is connected to the thermal optimum of growth and aerobic scope, was 19.3±0.3°C and the temperature with the highest maximal heart rate, a measure of the thermal limits of cardiac function, was 21.8±0.4°C in these fish (Anttila et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
“…However, in seabass acclimated to 17°C, Anttila et al (2017) found arrhythmia occurred at around 22°C, although CT max was above 30°C. Furthermore, the Arrhenius breakpoint temperature for maximum heart rate, which is connected to the thermal optimum of growth and aerobic scope, was 19.3±0.3°C and the temperature with the highest maximal heart rate, a measure of the thermal limits of cardiac function, was 21.8±0.4°C in these fish (Anttila et al, 2017). These findings support our conclusion that cold life-conditioned juvenile sea bass might be less able to cope with large acute temperature changes than their warm life-conditioned siblings.…”
Section: Discussionmentioning
confidence: 76%
“…To study the cardiac performance of trout during acute warming, maximum heart rate ( f Hmax ), temperature of peak heart rate ( T peak ), and the two transition temperatures, the Arrhenius break point temperature ( T abt ) and the arrhythmia temperature ( T arr ) of f Hmax were measured in vivo using electrocardiograms (ECGs) as previously described by Casselman et al (2012) and Anttila et al (2017) . The cardiovascular measurements of the fish were done within 7 days at the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In salmonids, the decline in AAS is mainly due to impairment of maximum heart rate (fH max ), which is associated to reduction in MMR and, thus, AAS at temperatures beyond T opt (Eliason and Anttila, 2017). At upper critical temperatures, besides a reduction in fH max , fish start to show cardiac arrhythmias which might lead to death if warming continues (Casselman et al, 2012;Anttila et al, 2017;Gilbert and Farrell, 2021;van der Walt et al, 2021). Farmed fish could be especially challenged by environmental warming since previous studies have shown that selection for fast-growth and sedentary aquaculture conditions are often associated with cardiac deformities and impaired cardiac performance (Gamperl and Farrell, 2004;Brijs et al, 2020;Frisk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Arrhenius breakpoint temperature (T ABP ) -the temperature at which the fH max first slows down its incremental rate with temperature -and arrhythmia temperature (T ARR ) -temperature at which fH max starts to become arrhythmic (Farrell, 2016). The T ABP and T ARR give estimates within 1-2°C for the optimum temperature of aerobic scope (T OPT ) and critical thermal maximum (CT MAX ), respectively (Casselman et al, 2012;Ferreira et al, 2014;Anttila et al, 2017;Gilbert and Farrell, 2021;van der Walt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%